Heart in Fours : Cardiology for Residents and Practitioners - Murthy Pothuri Radha Krishna; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2013)
The Heart in Fours: Cardiology for Residents and Practitioners provides students, residents and clinicians all the clinically useful information of cardiology. The book covers all diseases and abnormalities related to the heart by listing four key points for each topic. This pattern eventually facilitates a student, a teacher and a physician to recall to his memory, any piece of information without much effort. This book offers comprehensive knowledge on both theoretical and practical aspects of cardiology, explaining the causes, diagnosis, treatment and prevention of many cardiac complaints. It also covers topics such as cardiac catheterization, interventions in cardiology and cardiac surgery. The book also includes a chapter on pregnancy and cardiovascular disease.
Keywords: Cardiology; Electronic books